Teaching as Contemplative Professional Practice - Falkenberg, Thomas (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2012)
Starting with the argument that what we attend to is important for how we act in and on the world – and, thus, our moral living – the article conceptualizes teaching as contemplative practice, arguing that attending pre-conceptually and non-judgmentally to our inner life as teachers as we teach moment-by-moment will give us the basis upon which we can engage developmentally in teaching as a moral endeavour. Central to the conceptualization of teaching as contemplative professional practice is the idea of on-going wok on one’s awareness, attention, and noticing of one’s inner life while teaching. Such on-going professional development is undertaken in regard of others, the students, and, thus, makes teaching as contemplative practice a moral endeavour.